A parallel decoding algorithm of LDPC codes using CUDA - Shuang Wang; Cheng, S.; Qiang Wu (2008 42nd Asilomar Conference on Signals, Systems and Computers, 2008)
A parallel belief propagation algorithm for decoding low-density parity-check (LDPC) codes is presented in this paper based on Compute Unified Device Architecture (CUDA). As a new hardware and software architecture for addressing and managing computations, CUDA offers parallel data computing using the highly multithreaded coprocessor driven by very high memory bandwidth GPU. The parallel decoding algorithm, based on CUDA, allows that all bit-nodes or check-nodes work simultaneously, thus provides an efficient and fast way for implementing the decoder.